2004
DOI: 10.1007/s00270-004-0241-z
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular Intrahepatic Portosystemic Shunt (TIPS) in the Treatment of Venous Symptomatic Chronic Portal Thrombosis in Non-cirrhotic Patients

Abstract: Percutaneous techniques for portal recanalization are an interesting alternative even in non-acute thrombosis. Once flow has been restored in the portal vein TIPS may be necessary to obtain an adequate outflow, hence facilitating and maintaining the portal flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 20 publications
6
71
1
2
Order By: Relevance
“…In 23 of the 28 patients with complete portal vein thrombosis success was achieved in 73% including 6 of 9 patients with cavernomatous transformation. 165 Another study on TIPS performed on 15 patients with cirrhosis and PVT leading to refractory ascites, variceal hemorrhage and refractory pleural effusion showed its success in 75% (3/4) patients with cavernomatous transformation and 10/11 (94%) patients with acute PVT with an overall survival of 87%. It may thus be a treatment option in certain patients.…”
Section: Tipsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 23 of the 28 patients with complete portal vein thrombosis success was achieved in 73% including 6 of 9 patients with cavernomatous transformation. 165 Another study on TIPS performed on 15 patients with cirrhosis and PVT leading to refractory ascites, variceal hemorrhage and refractory pleural effusion showed its success in 75% (3/4) patients with cavernomatous transformation and 10/11 (94%) patients with acute PVT with an overall survival of 87%. It may thus be a treatment option in certain patients.…”
Section: Tipsmentioning
confidence: 99%
“…164 Studies have shown long term patency rates even without anticoagulation in TIPS, hence routine anticoagulant use may not be recommended after TIPS placement except in those patients with prothrombotic states. In a few cases with PVT, TIPS has been shown to be successful 165,166 in treating patients with portal biliopathy and portal vein thrombosis complicating Budd-Chiari syndrome. In 23 of the 28 patients with complete portal vein thrombosis success was achieved in 73% including 6 of 9 patients with cavernomatous transformation.…”
Section: Tipsmentioning
confidence: 99%
“…The tissue harmonic imaging mode was used to maximize the diagnostic effectiveness of baseline US. This specific technique uses a low applied acoustic pressure to produce images based on nonlinear acoustic interaction between the ultrasound system and microbubbles that oscillate and resonate, giving continuous contrast enhancement to gray-scale images [23]. SonoVue (Bracco, Milan) is a second-generation contrast agent consisting of stabilized microbubbles of sulfur hexafluoride gas [24].…”
Section: Us and Contrast-enhanced Usmentioning
confidence: 99%
“…In about 50%, restoration of portal blood fl ow is possible [115][116][117] . Patients with hepato-pulmonary syndrome [118][119][120] and patients with malignant portal hypertension [121] have been successfully treated with TIPS.…”
Section: Rare Indicationsmentioning
confidence: 99%